2012
DOI: 10.2174/1874282301206010049
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Tides and the Long-Term Variation of the Peak Latitude Anomaly of the Summer Sub-Tropical High Pressure Ridge over Eastern Australia

Abstract: This study looks for evidence of a correlation between long-term changes in the lunar tidal forces and the interannual to decadal variability of the peak latitude anomaly of the summer (DJF) subtropical high pressure ridge over Eastern Australia (L SA ) between 1860 and 2010. A simple "resonance" model is proposed that assumes that if lunar tides play a role in influencing L SA , it is most likely one where the tidal forces act in "resonance" with the changes caused by the far more dominant solar-driven season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Wilson [9] has extended the work of Li et al [7] by showing that the lunar atmospheric tides have an influence upon regional climate variables on inter-annual to decadal time scales. Wilson [9] has shown that variations in the peak latitude anomaly of the summer (DJF) subtropical high pressure ridge over Eastern Australia (L SA ) exhibits the same period and phase as that of the 18.6/ 9.3 year draconic spring tides.…”
Section: Introductionmentioning
confidence: 88%
“…Wilson [9] has extended the work of Li et al [7] by showing that the lunar atmospheric tides have an influence upon regional climate variables on inter-annual to decadal time scales. Wilson [9] has shown that variations in the peak latitude anomaly of the summer (DJF) subtropical high pressure ridge over Eastern Australia (L SA ) exhibits the same period and phase as that of the 18.6/ 9.3 year draconic spring tides.…”
Section: Introductionmentioning
confidence: 88%
“…Ralph's simplified picture of the intricate phenomena at stake serves a practical purpose and it completely fulfils this end. It is patently clear, however, that Ralph would be at a loss to explain long-term variations such as draconic spring tides, which occur roughly every 9.3 years (see Wilson 2012;Wilson and Sidorenkov 2013). Should we then assert, as Plato did nearly twenty-five centuries ago in the Theaetetus, that knowledge must be accompanied by an explanation?…”
Section: Epistemic Contextualismmentioning
confidence: 99%
“…The 206-day cycle is known in astronomy as half of the FMC. From a physics point of view, the 412-day cycle is the period of beats produced by interfering the close frequencies of anomalistic (27.55 days) and synodic (29.53 days) months (Sidorenkov, 2015;Sidorenkov, 2009;, Wilson, 2012 or the synodic month and the evection period in the lunar longitude (31.81 days). The important point to note is that the 206-day cycle is equal to the half-difference between the frequencies of the interfering oscillations as well as being a whole multiple of the synodic month (since 7 x 29.53 days = 206.7 days).…”
Section: Origin Of the 206-day Lunar Cyclementioning
confidence: 99%